Pembangunan Karakter Melalui Makanan yang Sehat - Ghifari Syafa Sukoco; Nurhayati Nurhayati; Rima Artanti; Najatul Aulia; Naila Tri Absari; Aidina futri ritonga; Aulia Ramadhani (Pusat riset dan Inovasi Nasional, 2025)
This study aims to examine the relationship between healthy food consumption and character development in students. The research is based on the premise that healthy eating plays a vital role not only in physical well-being but also in shaping students' behavior and moral values from an early age. A quantitative descriptive approach was used, employing a theoretical and conceptual analysis design. The findings indicate a strong relationship between healthy eating habits and the development of positive character traits such as discipline, responsibility, and honesty. Based on a regression analysis simulation, healthy food consumption was found to contribute approximately 46% to character formation. These results highlight the importance of integrating healthy eating patterns into character education programs both in schools and at home. The study recommends collaboration among schools, parents, and government bodies to promote healthy eating as a foundation for building strong and positive character in young generations.